Indirect to direct band gap crossover in two-dimensional WS2(1−x)Se2x alloys - Cyrine Ernandes (Nature Portfolio, 2021)
Abstract In atomically thin transition metal dichalcogenide semiconductors, there is a crossover from indirect to direct band gap as the thickness drops to one monolayer, which comes with a fast increase of the photoluminescence signal. Here, we show that for different alloy compositions of WS2(1−x)Se2x this trend may be significantly affected by the alloy content and we demonstrate that the sample with the highest Se ratio presents a strongly reduced effect. The highest micro-PL intensity is found for bilayer WS2(1−x)Se2x (x = 0.8) with a decrease of its maximum value by only a factor of 2 when passing from mono-layer to bi-layer. To better understand this factor and explore the layer-dependent band structure evolution of WS2(1−x)Se2x , we performed a nano-angle-resolved photoemission spectroscopy study coupled with first-principles calculations. We find that the high micro-PL value for bilayer WS2(1−x)Se2x (x = 0.8) is due to the overlay of direct and indirect optical transitions. This peculiar high PL intensity in WS2(1−x)Se2x opens the way for spectrally tunable light-emitting devices.